Comparative Analysis of The Performance of Bitcoin, Stocks, and Gold as Alternative Investments - Siti Hernita Oktavia; Indira Shofia; Abdul Rauf; Abdul Halik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The objective of this research is to examine and analyze the performance comparison among Bitcoin cryptocurrency, stocks, and gold. This study employs a quantitative research approach utilizing a comparative method. The population consists of the monthly closing prices of Bitcoin, LQ45 stocks, and gold from 2018 to 2023, totaling 180 data points. A saturated sampling technique is applied in this research. The study utilizes time series data, relying on secondary data sources. Data analysis is conducted using Microsoft Excel, applying relevant formulas for each variable. The data is further processed using SPSS, specifically employing the ANOVA test. The findings reveal significant differences in returns and risks among Bitcoin, stocks, and gold. Additionally, the performance metrics—measured by the Sharpe, Treynor, and Jensen methods—also indicate notable differences among these three asset classes.